Disseminated nocardiosis in a patient with alcoholic liver cirrhosis: a case report - Rewaa Alqurashi; Husam Alobida; Abdullah Albathi; Moneera Aldraihem (BMC Infectious Diseases, 2023)
Abstract Background Nocardia are Gram-positive, aerobic, filamentous bacteria that can cause localized or disseminated infections. Immunocompromised patients are at a higher risk of developing Nocardia infection and further dissemination of the disease. To date, limited data have documented the relationship between nocardiosis and alcoholic liver disease. Case presentation We report the case of a 47-year-old man with a known history of alcoholic liver cirrhosis. The patient presented to our emergency department with redness, swelling in the left eye, and diminished bilateral vision. Fundus examination of the left eye was obscured, while that of the right eye was consistent with subretinal abscess. Therefore, endogenous endophthalmitis was suspected. Imaging revealed two ring-enhancing lesions in the brain, and multiple bilateral small cystic and cavitary lung lesions. Unfortunately, the left eye eventually eviscerated due to the rapid progression of the disease. Cultures from the left eye were positive for Nocardia farcinica. The patient was started on imipenem, trimethoprim/sulfamethoxazole, and amikacin based on culture sensitivity. The patient’s hospitalization course was complicated by his aggressive and advanced condition, which led to his death. Conclusions Although the patient’s condition initially improved with the recommended antibiotic regimens, it led to death owing to the patient’s advanced condition. Early detection of nocardial infection in patients with typical or atypical immunosuppressive conditions may improve overall mortality and morbidity. Liver cirrhosis disrupts cell-mediated immunity and may increase the risk of Nocardia infection.